A long-term follow-up study of men born with very low birth weight and their reproductive hormone profile. (4th May 2018) - Hammar, Mats; Larsson, Erika; Bladh, Marie; Finnström, Orvar; Gäddlin, PO; Leijon, Ingemar; Theodorsson, Elvar; Sydsjö, Gunilla
ABSTRACT: Environmental factors during the fetal period may adversely affect reproductive functions in men being born with very low birth weight (VLBW, <1500 g). The objective of this prospective, controlled cohort study was to investigate if VLBW men have an altered reproductive hormone profile compared with men born at term. The study group initially consisted of all VLBW boys live-born between 1 February 1987 and 30 April 1988 in the south-east region of Sweden ( n  = 47). A control child was chosen born at term, at the same hospital, with the same parity, without malformations, and next in order after each VLBW child who survived the first four weeks ( n  = 45). The present follow-up was performed when the men were 26–28 years of age and included measurements of serum hormone levels, hair testosterone concentration, and anthropometric data. Also life-style questionnaires were collected from 26 VLBW men and 19 controls. The VLBW group ( n  = 26) had higher median levels of serum estradiol, 84.5 pmol/L than controls ( n  = 19), 57.5 pmol/L ( p  = 0.008). There was no significant correlation between serum estradiol and BMI ( r  = 0.06, p  = 0.74). There were no differences in other hormone levels or the reproductive pattern between the groups. In conclusion, even though there was a statistically significant difference in estradiol levels between the groups, both groups had low normal mean levels of questionable clinical significance. The reproductive pattern was similar in the two groups and in this study being born VLBW does not seem to affect these measured aspects of reproduction. Abbreviations : ADHD: attention deficit hyperactive disorder; AGA: average for gestational age; BMI: body mass index; CP: cerebral palsy; DHT: dihydrotestosterone; FSH: follicle stimulating hormone; LBW: low birth weight; LH: luteinizing hormone; SAD: sagittal abdominal diameter; SGA: small for gestational age; SHBG: sex hormone binding globulin; TSH: thyroid stimulating hormone; T3: triiodothyronine; T4: thyroxin; VLBW: very low birth weight